Effects Of Aquilaria Crassna Crude Extract On Simulated Ischemia Induced Cardiac Cell Death - PANADDA JERMSRI; ARUNYA JIRAVIRIYAKUL; SASIMANAS UNAJAK; SARAWUT KUMPHUNE (International Journal of Pharma and Bio Sciences, 2012)
To investigate the effect of ethylacetate extract of Aquilaria crassna Pierre ex Lecomte on simulated ischemia-induced cardiac cell injury and its mechanism on p38 MAPK activation. Rat cardiac myoblast cell line (H9c2), were subjected to 2 hours simulated ischemia (sI) and 24 hours of reperfusion, in the presence and absence of the ethyl acetate extract of Aquilaria crassna (A.Q.). The cellular injury and viability were determined. The result found that A.Q. at concentration 5 mg/ml was the most effective concentration to reduce cell death and injury. Then, cells were pre-treated with or without 5 mg/ml of A.Q. for 1 hour before, or at the beginning of 40 minutes-sI. Activation of p38 MAPK was measured by Western blot analysis. Treatment of A.Q. significantly reduced ischemia-induced p38 MAPK phosphorylation (p <0.05). In conclusion, treatment of 5 mg/ml of the ethylacetate extract of A. crassna reduced ischemia induced cell death by attenuating p38 MAPK phosphorylation.